Seasonal climatic niche and migration movements of Double‐crested Cormorants. Issue 8 (23rd August 2022) - King, D. Tommy; Wang, Guiming; Cunningham, Fred L.
Abstract: Avian migrants are challenged by seasonal adverse climatic conditions and energetic costs of long‐distance flying. Migratory birds may track or switch seasonal climatic niche between the breeding and non‐breeding grounds. Satellite tracking enables avian ecologists to investigate seasonal climatic niche and circannual movement patterns of migratory birds. The Double‐crested Cormorant ( Nannopterum auritum, hereafter cormorant) wintering in the Gulf of Mexico (GOM) migrates to the Northern Great Plains and Great Lakes and is of economic importance because of its impacts on aquaculture. We tested the climatic niche switching hypothesis that cormorants would switch climatic niche between summer and winter because of substantial differences in climate between the non‐breeding grounds in the subtropical region and breeding grounds in the northern temperate region. The ordination analysis of climatic niche overlap indicated that cormorants had separate seasonal climatic niche consisting of seasonal mean monthly minimum and maximum temperature, seasonal mean monthly precipitation, and seasonal mean wind speed. Despite non‐overlapping summer and winter climatic niches, cormorants appeared to be subjected to similar wind speed between winter and summer habitats and were consistent with similar hourly flying speed between winter and summer. Therefore, substantial differences in temperature and precipitation may lead to the climatic niche switching of fish‐eating cormorants, a dietary specialist, between the breeding and non‐breeding grounds. Abstract : We investigated seasonal climate niches of migratory double‐creased cormorants. We used the satellite‐telemetry locations of the same birds between summer and winter. Our findings suggest that double‐crested cormorants switched climate niches between the breeding and non‐breeding grounds.